Usina Hidrelétrica do Bem Querer: análise e projeção da influência do projeto no uso e cobertura do solo na Bacia do Médio Rio Branco, Roraima - Moraes, Eclair (2021)
The great development projects involving infrastructure construction, such as hydroelectric power plants, feature as common traits on local impacts, regional or territorial, typified as changes on population structure, like work, organization and land use, political framework, culture and ecosystems. In the Amazon, the government has designed and implemented the construction of several hydroelectric power plants (HPP). In this context, in the state of Roraima, it is intended to be built Bem Querer HPP, which is under environmental impact studies, causing debates about the socioenvironmental effects and its benefits in an economic perspective to the state. The present research intends to map soil use and cover in the area scope of the Bem Querer hydroelectric plant project, in the central region of Roraima; quantify the soil use and cover, elaborate an area change predictive model; and, at the end, discuss the possibilities of renewable energy sources in Roraima. For the development of this research, experimental and bibliographic research methods were used. To prepare the land use and land cover maps, CBERS-4 satellite images were used, applying Arcgis 10.1, QGIS 2.18.1 for data processing. In order to carry out the flooding effects projections for the Bem Querer HPP, land use, land cover and flood buffer zone data were used. The results point out that the influence area of the Bem Querer HPP is 2,433.98 Km², divided into six classes of land use and land cover, such as water bodies 5.76% (140.29 km²), urbanized area 2,08% (50.63 km²), sandbank 0,71% (17.28 km²), livestock and agricultural activity 20,84% (507.25km²), forest 54,20% (1319.24 km²) and savannah 16.40% (399.18km²). The predictive model of changes in land use and land cover affected by the reservoir will cover an area of 519.21 km², such as water bodies 24.57% (127.56 km²), urbanized area 0.01% (0.04 km²), sandbank 2.34% (12.12 km²), livestock and agricultural activity 11.06% (57.43 km²), forest 59.78% (310.36 km²) and savannah 2.25% (11.69 km²). With these results, it was possible to verify the possible changes and impacts to be caused by the Bem Querer HPP installation. At the end, the possibilities of renewable energy sources and new horizons for electric energy production in Roraima are also discussed.